Hydrilla: Florida's Worst Submersed Weed - Lyn A. Gettys; Stephen F. Enloe (EDIS)
Hydrilla, which was originally introduced to the state as an aquarium plant, was intentionally planted in canals by aquarium plant dealers in the 1950s and quickly escaped cultivation. In addition to being one of the world’s worst aquatic weeds, the species is Florida’s most intensively managed submersed plant. Hydrilla is a federally listed noxious weed and a prohibited aquatic plant in Florida, making cultivation, sale, and possession of the species illegal. This 7-page fact sheet discusses the classification, characteristics, habitat, and management of hydrilla. Written by Lyn A. Gettys and Stephen F. Enloe, and published by the UF Agronomy Department, February 2016.